Ten-Year Outcome of Topography-Guided Transepithelial Surface Ablation for Refractive Myopia Treatment - Branger, Giacomo Alessandro; Le, Minh Tu; Inauen, Lars Oliver; Reichmuth, Valentina; Kaufmann, Claude; Baenninger, Philipp (Klinische Monatsblätter für Augenheilkunde, 2022)
Background To evaluate 10-year long-term refractive visual stability and participantsʼ satisfaction in the refractive treatment of myopic eyes undergoing topography-guided transepithelial surface ablation using a 1KHz excimer laser.Patients and Methods This single-center prospective survey assessed participantsʼ satisfaction 10 years after the treatment using a non-validated questionnaire with regards to visual outcome, dry eye, and visual disturbance symptoms. Pre- and postoperative visual and refractive data were evaluated.Results Of 106 participants (54% females) with a mean patient age of 36 (± 8.6) years, 166 eyes were included. Mean preoperative spherical equivalent (SE) was − 4.23 (± 2.48) diopters (D). Uncorrected distant visual acuity (UCVA) after 10 years was ≥ 1.0 (Snellen) in 92% of the eyes. Manifest SE was within ± 1.0 D of the desired refraction in 86% of the eyes after 10 years. Mean quality of life (QOL) improvement was high (9.15 out of 10 points). Dry eye symptoms were reported by 35 out of 104 (34%) patients. Visual symptoms like halos or starbursts were reported by 24 out of 101 (24%) and 12 out of 100 (12%) patients, respectively.Conclusions Topography-guided transepithelial surface ablation for myopia provided stable long-term results in terms of UCVA and SE. Participant satisfaction was high, with only low rates of dry eye or visual symptoms.
Keywords: topography-guided transepithelial surface ablation; refractive myopia treatment; long term results; halo; starburst; questionnaire